Dampak Ekonomi Pengembangan Pariwisata Bagi Pelaku Usaha Lokal: Taman Wisata Alam Gunung Tangkuban Perahu (Fakultas Ekonomi Universitas Gresik, 2023)
The tourism industry plays an important role as a source of state income that contributes to national economic growth, especially in providing jobs and increasing state productivity. Tourism development is carried out to increase community income which is expected to help improve community welfare. Tourism development also helps accelerate the economic growth of a region. Tourism is inseparable from consumer demand in terms of consumption and investment, which ultimately leads to the procurement of goods and services. This study examines the economic impact of tourism development on local businesses in TWA Gunung Tangkuban Perahu using time series data from 2018-2023. This study used a qualitative descriptive approach model. The data studied was obtained from primary data through survey results and questionnaires on visitors and traders in the Tangkuban Perahu Mountain Nature Park environment. The results show that the TWA development strategy of Gunung Tangkuban Perahu contributes to the fulfilment of the 5A principle (Attraction, Accommodation, Accessibility, Amenity, and Activity) in tourism according to tourists. Tourism development positively affects the economic growth of the surrounding community. Tourism can provide employment, stimulate the growth of other industries and trigger local economic growth through various forms, including community income and attracting investment.